Empowerment of Medicinal Plant Gardens and Training on Herbal Tea Making based on Medicinal Plants in Wage Permai-Sidoarjo. - Nikmatul Ikhrom Eka Jayani; Karina Citra Rani; Arief Budhyantoro; Tjie Kok; Anita Dahliana (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
The Wage Permai Housing Complex in Sidoarjo Regency has a potential vacant land of approximately 1800 m2. Based on this potential, a community engagement program conducted by the University of Surabaya in collaboration with the Community Group (POKMAS) and the PKK cadre of Wage Permai was carried out to empower the land into a Medicinal Plant Garden (TOGA). The aim of this activity is to improve the health and economic productivity of the residents of Wage Permai. The program includes the establishment and empowerment of the TOGA garden, as well as training on herbal tea making. The methods applied in this program are participatory rural appraisal, community development, education, and participatory technology development. The results of this activity include the establishment of the Wage Permai Medicinal Plant Garden, which consists of around 23 medicinal plants. There was a significant increase in knowledge and skills of the PKK cadre of Wage Permai in herbal tea processing, as evidenced by the significant improvement in post-test results (p<0.05). The outputs of the herbal tea making training are two herbal tea product formulas and a book on herbal tea blending. These outputs are intended to support household-scale production to enhance the economic productivity of the residents.